Variation in the prevalence and abundance of acanthocephalans in brown-nosed coatis nasua Nasua and crab-eating foxes Cerdocyon thous in the Brazilian Pantanal - Gomes, A. P.N. (2019)
Host infection by parasites is influenced by an array of factors, including host and environmental features. We investigated the relationship between host sex, body size and age, as well as seasonality on infection patterns by acanthocephalan in coatis (Procyonidae: Nasua nasua) and in crab-eating foxes (Canidae: Cerdocyon thous) from the Brazilian Pantanal wetlands. Between 2006 and 2009, we collected faecal samples from these hosts and analyzed for the presence of acanthocephalan eggs. Prevalence, abundance and intensity of eggs of acanthocephalans were calculated. Egg abundance was analyzed using generalized linear models (GLM) with a negative binomial distribution and models were compared by Akaike criteria to verify the effect of biotic and abiotic factors. Prevalence of acanthocephalans was higher in the wet season in both host species but did not differ between host sexes; however, adult crab-eating foxes showed higher prevalence of acanthocephalan eggs than juveniles. In contrast, prevalence of acanthocephalan eggs found in coatis was higher in coati juveniles than in adults. Host age, season and maximum temperature were the top predictors of abundance of acanthocephalan eggs in crab-eating foxes whereas season and host sex were predictors of egg abundance in coatis. The importance of seasonality for abundance of acanthocephalan was clear for both host species. The influence of host-related attributes, however, varied by host species, with host gender and host age being important factors associated with prevalence and parasite loads.